The sociology of religion: a substantive and transdisciplinary approach - Lundskow, George N. (SAGE, 2008)
Lundskow's approach to the sociology of religion is to explore the facts of religion in its great diversity, all the most interesting beliefs and practices, and then to help students to learn relevant concepts that can be used to explain empirical observations